MARINE TOXINS (1940-2017) - MARANTE, FRANCISCO JAVIER TOLEDO; BENKOVICS, ALBA GONZÁLEZ (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2018)
Marine toxins are secreted by marine organisms in order to act as a deterrent against attack from predators, parasites and fouling organisms. This paper gives a historical overview of the discovery of these chemical compounds - marine toxins –from 1940 till 2017 and describes the chemical structure of the main toxic substances as well as the analytical methods used for their identification. The use of this method as a means of studying the interaction between marine organisms and their environment, as well as evaluating the function and health of organisms at a molecular level has a number of benefits. As a consequence, there has been an increase in the application of chemical structural analysis in the marine sciences. This study draws attention to how complex chemical interactions in the marine environment are and why in depth research is required.